Analysis of Syntactic Errors in Arabic Textbook-Based Instructional Materials and Their Implications for Arabic Learning at Madrasah Aliyah - Ma'suq, Ahmad Tarajjil; Huda, Mokhammad Miftakhul; Irawan, Bambang (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2024)
Textbooks are essential components in learning, but errors are often found, including syntax. It aims to analyze some of the errors found in the textbook used as a reference in learning Arabic at MA Madinatul Ulum and explain the implications of these errors on Arabic Learning. This research uses library research with an applied linguistic approach in error analysis. Data was collected using documentation techniques related to Arabic textbooks, books, journals, and other written works. The data analysis used is a content analysis technique with several steps: identifying, interpreting, and correcting. The research showed that significant syntactic errors were identified. However, the textbook covers various aspects of Arabic skills, such as listening, speaking, reading, and writing, with various cognitive, psychomotor, and affective tasks. These errors deviate from standard Arabic grammar norms, compromising instructional quality, affecting student evaluations, and posing challenges for teachers. By involving language experts in developing instructional materials, providing training for teachers, and promoting the use of alternative learning resources, it is hoped that syntactic errors in instructional materials can be minimized, thereby enhancing the quality of Arabic learning. Recommendations include thoroughly reviewing and improving materials to ensure adherence to educational standards emphasizing syntactic accuracy. Future research should expand to encompass broader aspects of Arabic instruction beyond syntax, encompassing morphology and semantics to enhance educational effectiveness